Detection of biofilm in bronchoalveolar lavage from children with non‐cystic fibrosis bronchiectasis. Issue 3 (18th March 2014) - Marsh, Robyn L.; Thornton, Ruth B.; Smith‐Vaughan, Heidi C.; Richmond, Peter; Pizzutto, Susan J.; Chang, Anne B.
Summary Background The presence of Pseudomonas aeruginosa biofilms in lower airway specimens from cystic fibrosis (CF) patients is well established. To date, biofilm has not been demonstrated in bronchoalveolar lavage (BAL) from people with non‐CF bronchiectasis. The aim of this study was to determine (i) if biofilm was present in BAL from children with and without bronchiectasis, and (ii) if biofilm detection differed between sequentially collected BAL. Methods Testing for biofilm in two sequentially collected BAL from children with and without bronchiectasis was done using BacLight™ live–dead staining and lectin staining for extracellular polymeric biofilm matrices. Bacterial culture and cytological measures were performed on the first and second lavages, respectively. Clinically important BAL infection was defined as >104 cfu of respiratory pathogens/ml BAL. Results Biofilm was detected in BAL from seven of eight (87.5%) children with bronchiectasis (aged 0.8–6.9 years), but was not detected in any of three controls (aged 1.3–8.6 years). The biofilms contained both live and dead bacteria irrespective of antibiotic use prior to bronchoscopy. Biofilm was detected more frequently in the second lavage than the first. Three of the seven biofilm‐positive BAL were culture‐positive for respiratory pathogens at clinically important levels. Conclusions Biofilm is present in BAL from children with non‐CF bronchiectasis even when BAL‐defined clinically important infection was absent. Studies to characterize lower airway biofilms and determine how biofilm contributes to bronchiectasis disease progression and treatment outcomes are necessary. Pediatr Pulmonol. 2015; 50:284–292. © 2014 Wiley Periodicals, Inc.